The Communicative Needs of the High Schools in Addis Ababa - Abiy, Yigzaw (The Ethiopian Journal of Education, 2025)
The purpose of this study is to identify the communicative needs of the high schools in Addis Ababa with respect to the language skills and the language activities. The study requires language skills and the language activities. The study requires information about the importance of language skills and language activities to the students, and the frequency rate of performance of language activities by the students in the course of their study. To achieve this aim, questionnaires were distributed to 64 teachers and 150 students; and interviews were administered to 10 teachers and 13 students. The teacher questionnaire aimed at investigating the important language skills and language activities. The results indicated that: - the macro-skills were important to the students in the course of their study in the order Listening-Reading-Writing and -Speaking; - the listening activities were important in the order listening to explanations-discussions-instructions and not making; - participating in discussions, asking questions, and answering questions were the important speaking activities in that order; - of the reading activities, readings of textbooks, other related materials, hand-outs, and assignments were important in that sequence; and - not making, answering questions in examinations and writing assignments were the important writing activities. The student questionnaire asked the students to rate their activity performance in the course of their study. The findings indicated that what were considered the most important activities by teachers were not, in most cases, the most frequent activities students performed. Interviewing teacher and students, it was found that the orders of importance and frequency of performance of the language skills and the language activities revealed in the questionnaires, except in few cases, were not the same. Although the orders of importance and frequency of performance varied between the two instruments, it was concluded that the language skills and the language activities are the common communicative needs of the high schools, and attempts were made to interpret the language activities into Munby’s micro-skills as resultant skills. On the basis of the study, it is mainly recommended that the language needs of learners (that is, content) should be studied. This study is only a partial work to develop a course. And it is recommended that textbooks should include the important language skills to enable the students to perform the activities. Selection of the language skills should be made by taking what the students have already known into account.